2008
DOI: 10.3346/jkms.2008.23.3.477
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Integrity of Corticocortical Tracts in Mild Cognitive Impairment: A Diffusion Tensor Imaging Study

Abstract: Mild cognitive impairment (MCI) has been defined as a transitional state between normal aging and Alzheimer disease. Diffusion tensor imaging (DTI) can estimate the microstructural integrity of white matter tracts in MCI. We evaluated the microstructural changes in the white matter of MCI patients with DTI. We recruited 11 patients with MCI who met the working criteria of MCI and 11 elderly normal controls. The mean diffusivity (MD) and fractional anisotropy (FA) were measured in 26 regions of the brain with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
66
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 25 publications
15
66
1
3
Order By: Relevance
“…A consistent finding in AD is an increase in MD [5] with a concomitant decrease in FA, with the majority of studies that report such differences in FA examining white matter. ROI-based DTI studies report decreased FA in several white matter tracts in AD, including the fornix [46,47], corpus callosum [48][49][50], and cingulum bundle [51][52][53] (as reviewed in [21]) similar to reduced FA indices reported here in 3xTg hippocampus. Interestingly, a previous DTI study of 3xTg mice [29] did not detect any differences in white matter pathology, as reported in AD.…”
Section: Discussionsupporting
confidence: 49%
“…A consistent finding in AD is an increase in MD [5] with a concomitant decrease in FA, with the majority of studies that report such differences in FA examining white matter. ROI-based DTI studies report decreased FA in several white matter tracts in AD, including the fornix [46,47], corpus callosum [48][49][50], and cingulum bundle [51][52][53] (as reviewed in [21]) similar to reduced FA indices reported here in 3xTg hippocampus. Interestingly, a previous DTI study of 3xTg mice [29] did not detect any differences in white matter pathology, as reported in AD.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, significantly reduced FA was recently reported in the inferior longitudinal fasciculus, a component of the sagittal stratum, of patients with mild cognitive impairment. 32 The observed differences in the spatial extent of WM dysfunction between the present SPMS study and those investigating RRMS allow for inference regarding the interplay of disease progression, WM integrity, and cognitive impairment. The SPMS cohort enrolled in the present study had a median EDSS score of 6.5, which is higher than prior TBSS studies that were all primarily or solely composed of patients with RRMS with a median EDSS score of 3 or less.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the DTI study results on MCI patients can be divided into two groups: 1) DTI studies on both amnesic and MCI "all subtypes" [23,40,41,84,85,88] that found no differences in MD and/or in FA in the CC compared with HC; and 2) the most recent studies [83,86,[89][90][91], which reported differences. One study on MCI "all subtypes" [89] found a significant change in MD and FA in the genu and the splenium of the CC in patients compared with HC.…”
Section: Diffusion-weighted Imaging and Diffusion Tensor Imaging Studiesmentioning
confidence: 99%
“…One study on MCI "all subtypes" [89] found a significant change in MD and FA in the genu and the splenium of the CC in patients compared with HC. Moreover, studies on amnesic MCI [83,86,90] mainly found a decreased FA and/or increased MD value in the splenium of the CC. Wang and colleagues [91] also reported a decreased FA value in the genu and the splenium and increased ADC in the genu of the CC (see Table 3 for technical details of the study).…”
Section: Diffusion-weighted Imaging and Diffusion Tensor Imaging Studiesmentioning
confidence: 99%